Lignin-based thermosetting film material as well as preparation method and application thereof

By directly dissolving lignin in an organic solvent and heating the reaction, the preparation process of lignin-based thermosetting film materials is simplified, the problems of complex process and irreversible chemical reactions in the prior art are solved, and the efficient preparation of the material and excellent mechanical properties are achieved.

CN119661879AActive Publication Date: 2025-03-21GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411758320.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

In the prior art, when preparing lignin-based thermosetting film materials, lignin needs to be modified and modified first, resulting in complex processes and irreversible chemical reactions that may occur.

Method used

By dissolving lignin in an organic solvent and/or an aqueous organic solvent solution, adding a crosslinking agent and heating the reaction, a lignin-based thermosetting film material is directly prepared, simplifying the process flow.

Benefits of technology

It realizes the efficient preparation of lignin-based thermosetting film materials, which have excellent mechanical properties, such as tensile strength up to 23.52MPa, elongation at break as high as 117.81%, toughness up to 12.31MJ/m3, and the process is simple and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661879A_ABST
    Figure CN119661879A_ABST
Patent Text Reader

Abstract

The invention discloses a lignin-based thermosetting film material as well as a preparation method and application thereof. The method comprises the following steps: dissolving lignin and a cross-linking agent in an organic solvent through a thermocuring method, carrying out a heating reaction to obtain a polymer solution, casting the polymer solution, and carrying out heating curing to obtain the independent cross-linked membrane. According to the preparation method disclosed by the invention, the lignin-based thermosetting film material can be prepared, the lignin-based thermosetting film material has relatively good mechanical properties, the tensile strength is 11.86 MPa, the elongation at break is 117.81%, and the toughness is 12.31 MJ / m < 3 >. The lignin-based film prepared by the invention is simple in preparation method, environment-friendly, green and degradable, and can be applied to the fields of mulching films, packaging materials, photo-thermal materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-value utilization of lignin, and specifically relates to a lignin-based thermosetting film material and a preparation method and application thereof. Background Art

[0002] Plastic film materials obtained from fossil resources have many characteristics such as light weight, low price, corrosion resistance, etc., and have been widely used in various fields of modern society. However, fossil resources are non-renewable resources, and the environmental problems caused by their difficulty in degradation are threatening human health and the ecological environment. Therefore, bio-based film materials with low R&D costs and wide applications have received widespread attention.

[0003] Lignin is one of the three major components of woody biomass and the second most abundant renewable natural polymer. It is low-cost and has antioxidant, biodegradable and UV-blocking properties. It is a good bio-based polymer material to replace petroleum-derived polymer materials. It is of great significance to develop lignin-based film materials with excellent performance.

[0004] From a molecular level, thin film materials need to be long and regular chain molecular structures, but lignin usually has poor performance due to its complex structure and brittleness. The current strategies for using lignin in the preparation of membrane materials include modifying lignin or compounding it with other polymers. In recent years, researchers have been committed to preparing thermosetting materials of lignin through chemical cross-linking of lignin. Gioia et al. (Gioia C, Colonna M, Tagami A, et al. Lignin-based epoxyresins: unravelling the relationship between structure and material properties [J]. Biomacromolecules, 2020, 21 (5).) prepared thermosetting films starting from alkaline lignin, which was first fractionated by sequential solvent extraction, then modified with epichlorohydrin, and finally reacted with poly (propylene oxide) diamine crosslinker. Chumakov et al. (Chumakov AP, Brett CJ, Schwartzkopf M, et al. Exploring the Effects of Different Cross-Linkers on Lignin-Based Thermoset Properties and Morphologies[J]. ACS Sustainable Chemistry & Engineering, 2021.) prepared thermosetting films using isolated alkali lignin, which were subsequently modified by reaction with allyl chloride and then cross-linked using a multifunctional thiol cross-linker.

[0005] In the prior art, lignin is generally modified or compounded with other polymers before being used to prepare film materials. This may be accompanied by irreversible and uncontrolled chemical reactions, and the preparation process is cumbersome and the operation is complicated. Summary of the invention

[0006] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a lignin-based thermosetting film material.

[0007] Another object of the present invention is to provide a lignin-based thermosetting film material prepared by the above preparation method.

[0008] Another object of the present invention is to provide an application of the above-mentioned lignin-based thermosetting film material.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a lignin-based thermosetting film material comprises the following steps:

[0011] The lignin is dissolved in an organic solvent and / or an organic solvent aqueous solution, a cross-linking agent is added, and the mixture is heated to react to obtain a polymer solution, which is then cast into a mold and heated to cure to obtain a lignin-based film material.

[0012] Preferably, the lignin is at least one of alkali lignin, enzymatic lignin and lignin sulfonate; more preferably, it is at least one of alkali lignin, enzymatic lignin and sodium lignin sulfonate; most preferably, it is alkali lignin.

[0013] Preferably, the organic solvent is at least one of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP) and N-vinylpyrrolidone (NVP); the organic solvent aqueous solution is at least one of γ-valerolactone (γ-GVL) aqueous solution, propylene carbonate (PC) aqueous solution and ethylene carbonate (EC) aqueous solution; the mass concentration of the organic solvent in the organic solvent aqueous solution is 50-70wt.%.

[0014] More preferably, the organic solvent is at least one of dimethyl sulfoxide (DMSO) and N-methylpyrrolidone (NMP); the organic solvent aqueous solution is a γ-valerolactone (γ-GVL) aqueous solution; and the concentration of the organic solvent in the organic solvent aqueous solution is 60 to 70 wt.%.

[0015] Preferably, the crosslinking agent is a diglycidyl ether; more preferably, it is at least one of 1,4-butanediol diglycidyl ether (BDDE), polyethylene glycol diglycidyl ether (PEGDE) and bisphenol F diglycidyl ether (BFGDE), wherein the molecular weight of polyethylene glycol diglycidyl ether is 400 to 1000; most preferably, it is at least one of 1,4-butanediol diglycidyl ether (BDDE) and polyethylene glycol diglycidyl ether (PEGDE); most preferably, polyethylene glycol diglycidyl ether (PEGDE) has a molecular weight of 500 to 1000.

[0016] Preferably, the mass fraction of the lignin in the organic solvent and / or the organic solvent aqueous solution is 10-40%; more preferably 20-40%; most preferably 20-30%.

[0017] Preferably, the mass ratio of the lignin to the cross-linking agent is (1-4):1; more preferably (2-4):1.

[0018] Preferably, the heating reaction is carried out at a temperature of 80 to 90° C. and for a time of 2 to 3 hours.

[0019] Preferably, the heating and curing procedure is: first keep warm at 75-85°C for 0.5-1h, then keep warm at 95-105°C for 0.5-1h, and finally keep warm at 115-125°C for 4-10h; more preferably: keep warm at 75-85°C for 0.5-1h, then keep warm at 95-105°C for 0.5-1h, and finally keep warm at 115-125°C for 6-10h; most preferably: keep warm at 75-85°C for 0.5-1h, then keep warm at 95-105°C for 0.5-1h, and finally keep warm at 115-125°C for 6-7h.

[0020] A lignin-based thermosetting film material is prepared by the preparation method.

[0021] Application of the above-mentioned lignin-based thermosetting film material.

[0022] More preferably, the lignin-based thermosetting film material is used in ground films, packaging materials and photothermal materials.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] The preparation method of the present invention does not need to modify the lignin raw material first, and directly uses industrially produced lignin. The process is simple. The diepoxy structure of the cross-linking agent is opened by heating, and cross-linked with the phenolic hydroxyl group of lignin during the curing process to form a dense three-dimensional ether network structure. The prepared lignin-based thermosetting film has excellent mechanical properties, wherein the tensile strength is as high as 23.52MPa, the elongation at break is as high as 117.81%, and the toughness is as high as 12.31MJ / m 3 ; And the most preferred γ-valerolactone has low volatility in aqueous solution, stable chemical properties, and good biocompatibility. It is a green, environmentally friendly, and highly safe organic solvent for the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a picture of the finished product of the lignin-based thermosetting film material prepared in Example 1.

[0026] Figure 2 In the figure a and b are cross-sectional SEM images of the lignin-based thermosetting film materials prepared in Examples 4 and 14, respectively.

[0027] Figure 3 In the figure, a and b are respectively the stress-strain performance diagram and toughness diagram of the lignin-based thermosetting film material prepared in Examples 1-6. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0029] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.

[0030] Example 1

[0031] Alkali lignin was added to DMSO at a mass fraction of 20%, and after stirring and dissolving evenly, BDDE cross-linking agent was added, wherein the mass ratio of lignin to the cross-linking agent was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silicone mold and kept on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 6 hours to make a lignin-based film material with a tensile strength of 10.34MPa, an elongation at break of 30.43%, and a toughness of 2.72MJ / m 3 .

[0032] Embodiment 2-6

[0033] The organic solvent used in Example 2 is NMP, and the rest is the same as in Example 1. Among them, the tensile strength is 15.05 MPa, the elongation at break is 28.30%, and the toughness is 3.61 MJ / m 3 .

[0034] The organic solvent used in Example 3 is NVP, and the rest is the same as in Example 1. Among them, the tensile strength is 2.54 MPa, the elongation at break is 33.7%, and the toughness is 0.65 MJ / m 3 .

[0035] The organic solvent used in Example 4 is a γ-GVL aqueous solution, wherein the mass concentration of γ-GVL is 70wt.%, and the rest is the same as in Example 1. Among them, the tensile strength is 23.52MPa, the elongation at break is 22.25%, and the toughness is 4.21MJ / m 3 .

[0036] The organic solvent used in Example 5 is a PC aqueous solution, wherein the mass concentration of PC is 50wt.%, and the rest is the same as in Example 1. Among them, the tensile strength is 6.36MPa, the elongation at break is 7.64%, and the toughness is 0.29MJ / m 3 .

[0037] The organic solvent used in Example 6 is EC aqueous solution, wherein the mass concentration of EC is 70wt.%, and the rest is the same as in Example 1. Among them, the tensile strength is 9.97MPa, the elongation at break is 11.79%, and the toughness is 0.78MJ / m 3 .

[0038] Example 7

[0039] The enzymatically hydrolyzed lignin was added to the γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 20%, and after being stirred and dissolved evenly, a BDDE cross-linking agent was added, wherein the mass ratio of lignin to the cross-linking agent was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and kept on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 6 hours to prepare a lignin-based film material with a tensile strength of 13.23MPa, an elongation at break of 17.08%, and a toughness of 1.79MJ / m 3 .

[0040] Example 8

[0041] Sodium lignin sulfonate was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 20%, and after being stirred and dissolved evenly, a BDDE crosslinking agent was added, wherein the mass ratio of lignin to the crosslinking agent was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and kept on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 6 hours to prepare a lignin-based film material with a tensile strength of 3.37MPa, an elongation at break of 50.32%, and a toughness of 1.13MJ / m 3 .

[0042] Example 9

[0043] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 10%, and after being stirred and dissolved evenly, a BDDE crosslinker was added, wherein the mass ratio of lignin to the crosslinker was 1:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and maintained on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 4 hours to prepare a lignin-based film material with a tensile strength of 12.13MPa, an elongation at break of 9.48%, and a toughness of 0.75MJ / m 3 .

[0044] Example 10

[0045] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 30%, and after stirring and dissolving evenly, a BDDE crosslinker was added, wherein the mass ratio of lignin to the crosslinker was 3:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and maintained on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 8 hours to prepare a lignin-based film material with a tensile strength of 21.80MPa, an elongation at break of 20.11%, and a toughness of 3.32MJ / m 3 .

[0046] Embodiment 11

[0047] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 40%, and after being stirred and dissolved evenly, a BDDE crosslinker was added, wherein the mass ratio of lignin to the crosslinker was 4:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and kept on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 10 hours to prepare a lignin-based film material with a tensile strength of 17.25MPa, an elongation at break of 24.55%, and a toughness of 3.57MJ / m 3 .

[0048] Example 12

[0049] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 20%, and after being stirred and dissolved evenly, a BDDE crosslinker was added, wherein the mass ratio of lignin to the crosslinker was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and maintained on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 7 hours to prepare a lignin-based film material with a tensile strength of 20.52MPa, an elongation at break of 23.0%, and a toughness of 3.83MJ / m 3 .

[0050] Example 13

[0051] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 20%, and after stirring and dissolving evenly, a BFDGE crosslinker was added, wherein the mass ratio of lignin to the crosslinker was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and maintained on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 4 hours to prepare a lignin-based film material with a tensile strength of 23.11MPa, an elongation at break of 18.81%, and a toughness of 2.52MJ / m 3 .

[0052] Embodiment 14

[0053] Alkali lignin was added to a γ-GVL aqueous solution (the mass concentration of γ-GVL was 70wt.%) at a mass fraction of 20%, and after being stirred and dissolved evenly, a PEGDE crosslinker (molecular weight of 500) was added, wherein the mass ratio of lignin to the crosslinker was 2:1, and the reaction was heated in an 80°C oil bath for 2 hours to obtain a polymer solution, which was then cast into a silica gel mold and kept on a heating plate at 80°C for 30 minutes, then at 100°C for 30 minutes, and finally at 120°C for 7 hours to prepare a lignin-based film material with a tensile strength of 11.86MPa, an elongation at break of 117.81%, and a toughness of 12.31MJ / m 3 .

[0054] Performance Testing

[0055] (1) Morphology of lignin film

[0056] The cross-sections of the lignin-based thermosetting film materials obtained in Examples 4 and 14 were subjected to SEM testing, and the SEM images obtained were respectively Figure 2 As shown in a and b.

[0057] The test results show that the lignin-based thermosetting film material is densely cross-linked, and no holes are observed. In comparison, the cross-section of the lignin-based thermosetting film material made by the BDDE cross-linker shows brittleness; the cross-section of the lignin-based thermosetting film material made by the PEGDE cross-linker is smoother and softer. This may be due to the influence of the molecular chain length of the cross-linker on the performance. The three-dimensional network formed by the cross-linking of the short molecular chain cross-linker is tight, making the material more rigid; the three-dimensional network formed by the cross-linking of the long molecular chain cross-linker is distant, making the material more flexible. The BDDE cross-linker has a short molecular chain, and the resulting film material has good tensile strength, which is characterized by rigidity and toughness; while the PEGDE cross-linker has a long molecular chain, and the resulting film material has a good elongation at break, which is characterized by flexibility.

[0058] (2) Mechanical properties of lignin films

[0059] The mechanical properties of the lignin-based thermosetting film materials prepared in Examples 1-6 were tested, and the stress-strain diagram and toughness diagram obtained were respectively Figure 3 As shown in a and b.

[0060] The test results show that the mechanical properties of lignin-based thermosetting film materials prepared by dissolving lignin with different solvents are different. Among them, the lignin-based thermosetting film material prepared by dissolving lignin with γ-GVL aqueous solution has the best mechanical properties, with a tensile strength of 23.52MPa, an elongation at break of 22.25%, and a toughness of 4.21MJ / m 3 This may be because the γ-GVL aqueous solution is conducive to the breaking of strong hydrogen bonds in lignin and the combination of aromatic core and aliphatic chain regions, which makes lignin better cross-linked with the cross-linking agent to form a three-dimensional network structure, preventing the movement of polymer chains, making the material stronger, and increasing the strength of the material's mechanical properties.

[0061] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a lignin-based thermosetting film material, characterized in that: The following steps are involved: The lignin is dissolved in an organic solvent and / or an organic solvent aqueous solution, a cross-linking agent is added, and the mixture is heated to react to obtain a polymer solution, which is then cast into a mold and heated to cure to obtain a lignin-based film material.

2. The method for preparing a lignin-based thermosetting film material according to claim 1, characterized in that: The organic solvent is at least one of dimethyl sulfoxide, N-methylpyrrolidone and N-vinylpyrrolidone; The organic solvent aqueous solution is at least one of a γ-valerolactone aqueous solution, a propylene carbonate aqueous solution and an ethylene carbonate aqueous solution; the concentration of the organic solvent in the organic solvent aqueous solution is 50 to 70 wt.%; The mass fraction of the lignin in the organic solvent and / or the organic solvent aqueous solution is 10-40%.

3. The method for preparing a lignin-based thermosetting film material according to claim 1 or 2, characterized in that: The organic solvent is at least one of dimethyl sulfoxide and N-methylpyrrolidone; The organic solvent aqueous solution is a γ-valerolactone aqueous solution; the concentration of the organic solvent in the organic solvent aqueous solution is 60-70wt.%; The mass fraction of the lignin in the organic solvent and / or the organic solvent aqueous solution is 20-40%.

4. The method for preparing a lignin-based thermosetting film material according to claim 1 or 2, characterized in that: The cross-linking agent is diglycidyl ether; the mass ratio of the lignin to the cross-linking agent is (1-4):

1.

5. The method for preparing a lignin-based thermosetting film material according to claim 4, characterized in that: The cross-linking agent is at least one of 1,4-butanediol diglycidyl ether, polyethylene glycol diglycidyl ether and bisphenol F diglycidyl ether, wherein the molecular weight of polyethylene glycol diglycidyl ether is 400-1000; or the cross-linking agent is at least one of 1,4-butanediol diglycidyl ether and polyethylene glycol diglycidyl ether; The mass ratio of the lignin to the cross-linking agent is (2-4):

1.

6. The method for preparing a lignin-based thermosetting film material according to claim 1 or 2, characterized in that: The lignin is at least one of alkali lignin, enzymatic lignin and lignin sulfonate.

7. The method for preparing a lignin-based thermosetting film material according to claim 1 or 2, characterized in that: The heating reaction temperature is 80-90°C and the time is 2-3h; The heating and curing procedure is: first keep the temperature at 75-85° C. for 0.5-1 h, then keep the temperature at 95-105° C. for 0.5-1 h, and finally keep the temperature at 115-125° C. for 4-10 h.

8. The method for preparing a lignin-based thermosetting film material according to claim 7, characterized in that: The heating and curing procedure is: keep warm at 75-85° C. for 0.5-1 h, keep warm at 95-105° C. for 0.5-1 h, and finally keep warm at 115-125° C. for 6-10 h.

9. A lignin-based thermosetting film material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the lignin-based thermosetting film material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of industrial alkali lignin / polyvinyl alcohol cross-linked thin film

    CN103467759A

  • Bio-based composite material containing lignin and preparation method therefor

    WO2022007496A1